Theory of Space Quantization (TSQ) Driven Superseding Theory of Newton’s Laws of Motion (Global Journal of Science Frontier Research, 2025)
The newly discovered Theory of Space Quantization TSQ is a unifying theory that brings together conventional Newtonian physics thermodynamics quantum physics quantum mechanics theories of gravitation and the theories of relativity under a single framework while also reshaping them All these theories were proposed without considering thermodynamics and the quantized nature of space-time or time-space in the universe
Keywords: theory of space quantization (TSQ); quantized time-space; thermodynamic consistency; newtonian physics limitations